Digital Technology in Higher Education: Integrating Learning Analytics and Adaptive E-Learning to Improve the Quality of Student Learning - Robet H Silaban; Muhammad Irfan Sarif; Perianus Lombu; Aldy Agustian; Larasati Rince Pratita Ritonga (Sean Institute, 2026)
This study aims to analyze the influence of digital technology through the integration of learning analytics and adaptive e-learning on the quality of student learning in higher education. The study used a quantitative approach with an explanatory research type. Data were collected through a Likert-scale questionnaire to 120 students who use digital learning systems. The data analysis technique used multiple linear regression with the help of statistical software. The results of the study showed that learning analytics and adaptive e-learning partially and simultaneously had a positive and significant effect on the quality of student learning, with a significance value of 0.000 < 0.05. The coefficient of determination (R²) value of 0.62 indicates that 62% of the quality of learning is influenced by these two variables. This technology integration has been proven to increase student engagement, effectiveness, and learning outcomes. Thus, the application of learning analytics and adaptive e-learning can be an effective strategy in improving the quality of learning in higher education.